On Some Issues of Handprints Detection and the Mechanism of Trace Formation on Porous Surfaces - V. A. Vasil’ev; T. A. Ermakova; Yu. A. Druzhinin; I. B. Afanas’ev; T. Yu. Yudina; E. Yu. Rusanov (Теория и практика судебной экспертизы)
Problems of detecting sweat and grease deposits on porous surfaces are common for forensic practice, and usually, they are successfully resolved with the help of chemical methods. Meanwhile, the interaction process in the system “porous surface – deposit – chemical agent" concerning clarification and identification of the trends within chemical reaction is not reviewed in literature sufficiently. For more comprehensive research of this process, the authors of the article have conducted multiple experiments on the ninhydrin reaction with the sweat and grease of the deposits, analyzed the interaction of the chemical agent with the sweat and grease, with the properties of porous (paper) materials using electron microscopy, and also looked into the display features of pore and edgeoscopic signs in the deposits under different storage conditions.As a result of the research, it is shown that such parameters of deposits carriers (paper) as porosity and hydrophilic properties and ambient humidity as well as the time of storage have a significant influence on the process of detecting the sweat and grease deposits on porous surfaces and their quality.